Hierarchical Assembly of an Interlocked M8L16 Container. Issue 19 (22nd March 2018) - Bloch, Witold M.; Holstein, Julian J.; Dittrich, Birger; Hiller, Wolf; Clever, Guido H.
Abstract: The self‐assembly of eight Pd II cations and sixteen phenanthrene‐derived bridging ligands with 60° bite angles yielded a novel M8 L16 metallosupramolecular architecture composed of two interlocked D 4 h ‐symmetric barrel‐shaped containers. Mass spectrometry, NMR spectroscopy, and X‐ray analysis revealed this self‐assembled structure to be a very large "Hopf link" catenane featuring channel‐like cavities, which are occupied by NO3 − anions. The importance of the anions as catenation templates became imminent when we observed the nitrate‐triggered structural rearrangement of a mixture of M3 L6 and M4 L8 assemblies formed in the presence of BF4 − anions into the same interlocked molecule. Furthermore, the densely packed structure of the M8 L16 catenane was exploited in the preparation of a hexyloxy‐functionalized analogue, which further self‐assembled into vesicle‐like aggregates in a reversible manner. Abstract : The missing link : A 24‐component Pd8 L16 catenane composed of two interlocked Pd4 L8 barrel‐shaped containers has been synthesized. NO3 − anions act as templates and can also trigger the transformation of Pd4 L8 monomers into the same interlocked molecule. When functionalized with hexyloxy chains, the densely packed catenane further self‐assembles into vesicle‐like structures in a reversible manner.